Role of HuR, AUF1 and zeta-crystallin in mediating pH-responsive increase in renal phosphoenolpyruvate carboxykinase (PEPCK) mRNA abundance in kidney cells - Gummadi, Lakshmi, author; Curthoys, Norman P., advisor; Nyborg, Jennifer K., committee member; Laybourn, Paul J., committee member; Wilusz, Carol J., committee member (Colorado State University. Libraries, 2012)
The maintenance of blood acid-base balance is essential for survival. However, metabolic acidosis is a common clinical condition that is characterized by a significant decrease in plasma pH and bicarbonate concentration. This alteration is caused by genetic or acquired defects in metabolism, in renal handling of bicarbonate, and in the excretion of titratable acid. In addition, metabolic acidosis could pose a secondary complication in patients with cachexia, trauma, uremia, end stage renal disease, osteomalacia, HIV infection and in patients with degenerative diseases. Increased renal ammoniagenesis and gluconeogenesis from plasma glutamine constitute an essential physiological response to metabolic acidosis that partially restores acid-base balance. A portion of this adaptive response is the rapid and pronounced increase in the cytosolic isoform of phosphoenolpyruvate carboxykinase (PEPCK) that occurs within the renal proximal convoluted tubule. Previous in vitro biochemical studies have mapped the binding of AUF1, HuR and ζ-crystallin (ζ-Cryst) to various AU-rich sequences within the 3'UTR of PEPCK mRNA. This response is reproduced in LLC-PK1-F+9C cells that are treated with acidic (pH 6.9) medium. It is mediated, in part, by stabilization of PEPCK mRNA. Here I have used a combination of approaches to characterize the dynamic interaction of trans-acting factors with the cis-acting elements in mediating the pH-responsive stabilization of PEPCK mRNA. In chapter III I show that binding of HuR and AUF1 have opposite effects on basal expression, but their co-ordinate interaction is required to mediate the pH-responsive adaptation. Consistent with this, while the individual recruitment of a chimeric protein containing the MS2 coat protein and either HuR or p40AUF1 failed to produce a pH-responsive stabilization, the concurrent expression of both chimeric proteins was sufficient to produce a pH-responsive increase in the half-life of the reporter mRNA. This study also demonstrated that HuR and AUF1 underwent profound altered post-translational modifications when LLC-PK1-F+9C cells were switched from basal to acid-pH medium conditions. In Chapter IV I went on to demonstrate that HuR makes direct interaction with PEPCK mRNA and that HuR/ AUF1 form hetero-oligomeric complex in an RNA-dependent manner. Finally in Chapter V I investigated the functional significance of the ζ-Cryst binding to the PEPCK-3'UTR. These experiments suggested that ζ-Cryst may serve as a key co-factor along with HuR and AUF1 to restrict the basal expression and that only HuR and AUF1 are required for the pH-responsive increase of PEPCK mRNA. Based upon the findings of the current study, I proposed a model depicting the co-ordinate role of HuR, AUF1 and ζ-Cryst in post-transcriptional regulation of PEPCK mRNA turnover and, more importantly in mediating the sustained pH-responsive increase of PEPCK mRNA. Under normal acid-base conditions, phosphorylated HuR, covalently modified AUF1 and ζ-crystallin are co-recruited to the 3'-UTR of PEPCK mRNA and may form a complex through direct protein-protein interactions. The binding of the three RNA-binding proteins leads to recruitment of a deadenylase that removes the poly-A tail and leads to the subsequent decapping and 5'→3' decay of the deadenylated PEPCK mRNA. However onset of metabolic acidosis leads to alterations in post-translational modifications including decreased phosphorylation of HuR and an increased phosphorylation of AUF1. These changes may promote the dissociation of ζ-crystallin from the RNA-binding complex. This remodeling of the ribonucleoprotein-complex blocks the association of deadenylases and maintains a poly-A tail that is well protected by the poly-A binding protein (PABP). Therefore, this remodeling of the protein/mRNA complex mediates the enhanced stabilization and translation of PEPCK mRNA.
Keywords: 2D gel electrophoresis; RNA binding proteins; MS2 recruitment; mRNA stabilization; metabolic acidosis; siRNA knockdown